Media writing : a practical introduction - Batty, Craig (Palgrave Macmillan, 2016)
"A new edition of a lively and critically-enriched guide to writing for the media in a range of different professional contexts. Combining theory with practical techniques, this original text caters for students seeking to hone their skills in areas as diverse as journalism, PR, copywriting and screenwriting"--